Analisis Implementasi Teori Hukum Inklusif dalam Pembentukan Undang-Undang yang Pancasilais di Indonesia - Siregar, Mardona; Mustafid, Mustafid (JOM, 2024)
The formation of laws in Indonesia requires a holistic approach to ensure that the resulting legal products are not only legally valid but also in line with the values ​​of Pancasila as the foundation of the state. This study aims to analyze the application of inclusive legal theory in the Pancasilaist legislative process. Inclusive legal theory recognizes the diversity of legal sources, including positive law, customs, religion, and other social norms, which are relevant in pluralistic Indonesia. This study uses a qualitative method with a normative and descriptive-analytical approach that aims to describe how inclusive legal theory is implemented in forming laws in Indonesia and analyze the suitability of applying the theory to the values ​​of Pancasila. Data were collected through document studies, literature studies, and in-depth interviews with legal experts and practitioners. Data analysis was conducted using qualitative techniques. This analysis will focus on how Pancasila values ​​are integrated into laws by applying Inclusive Legal Theory. The results of the study indicate that the application of inclusive legal theory in the formation of laws can increase public acceptance and compliance with the law because this approach takes into account and integrates various sources of law that exist in society, such as social norms, customs, religious values, and morality. The values ​​of Pancasila are reflected in the legislative process, which creates legal products that are fairer, more humane, and meet the needs of society. This study provides concrete recommendations for policymakers to improve the quality of legislation in Indonesia through a more inclusive approach based on Pancasila values. Thus, this study contributes to the development of inclusive legal theory and provides practical guidance for forming laws that are more effective for the identity of the Indonesian nation.